Ethics Noir in LA - Cañas Pelayo, Marcos Rafael (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2021)
On the occasion of its twentieth anniversary, Mulholland Drive maintains the moral enigmas that make it the subject of a wide range of interpretations. This David Lynch´s movie is the fight between fantasy and reality with elements from ethics and romanticism. What moral lessons can we learn from this cult movie? The blend of an unreal oneiric world and the classical tragedy results in a riveting experience for the audience, the critics, philosophical studies on film and anyone fascinated by narrative experimentation. A reading of the film considering the previous researches on Lynch´s mysterious work is proposed. The history of Betty/Diane Selwyn -a dual identity- is an opportunity to reflect on the human condition, its contraditions and its dilemmas. From its premiere in 2001 until nowadays, Mulholland Drive´s spectators are led to question everything they thought they knew about it.